Hubungan Antara Motivasi Dengan Prestasi Belajar Bidang Studi Pendidikan Agama Islam - Bahtiar Hariyadi (EDUCATIO : Journal of Education, 2016)
This research is to find out if there is an accomplished motivational relationship with the results of learning the Islamic Religious Education elementary school students Wawonggole Kec. Unaaha Kab. Konawe. The research method used is a type of quantitative descriptive research method by using a survey pattern. Data collection techniques using observation techniques, Angket and documentation. The analysis used in this study is the correlation analysis of product moment. Calculation results by using the product moment correlation formula and a simple regression found the value rxy = 0.655 While the value of the coefficient of determination (R2) is at 42.928% the value of the coefficient of determination obtained indicates that the achievement Studied Islamic religious education students of 42.92%, determined by the motivation of learning students, while the rest is 57.072% determined by other variables that are not researched. Based on a significant 5% confidence level test with DK = n – 2, 30-2 = 28, value = 0.404 because Thitung = 10.055 > this = 0.404, then Ho is rejected and received H1. Using the rules of testing: thus it can be concluded that there is a significant link between motivating students learning with the learning achievement of Islamic religious education.Education and good motivation applied by Islamic religious education teachers will improve student learning achievement